Renewable Micro off-Grid System for Rural District using Iot System - Udoh et al., Anthony Ogochukwu (International Journal of Advanced Science and Technology, 2020)
In this paper, the renewable micro off-grid system for rural district regionis proposed. The proposed system consists of three renewable sources as follows: wind, solar and hydroelectric sources. The investigation is conductedusing appropriate tools and converters to construct the micro grid and external batteries will be available if thereis a lack of supplyfrom the renewable source. The components that will be used during the construction of the rural house will be selected on the consumption data for the house which the amount of power generated from each renewable source. A costanalys is will be done before all the components are installed as it is an important factor for the rural areas. IOT system will be a cloud-based system where all the data will be transferred from the renewable sources and the energy that is being consumed by the consumers.